Application of pinch-and-swell structure rheology gauge to determine rock paleo-rheological parameters in Taili, western Liaoning, NE China. (15th May 2017) - Sun, Zhengquan; Zeng, Zuoxun; Wu, Linbo; Xu, Shaopeng; Yang, Shuang; Chen, Deli; Wang, Jianxiu
Highlights: 86 boudin layers were selected and measured in the study area. Related parameters were calculated using pinch-and-swell structure rheology gauge. The rheological property of rock is influenced by mineral assemblage and structure. The rheology gauge of rock is important to obtain the rheological information. Abstract: New results, in combination with previously published ones, reveal that when the Stress Exponent of the Competent layer (SEC) ranges from 1 to 10 (1 < n < 10), Pinch-and-Swell structure Rheology Gauge (PSRG) can only be available under the condition that the Viscosity ratio between the Competent layer and its corresponding Matrix layer (VCM) is larger than 10. Therefore, we made the attempt to calculate the viscosity ratio of pinch-and-swell structure of competent layer to the related matrix and stress exponent. Based on this knowledge, we applied this gauge to calculate SECs and VCMs of eight types of pinch-and-swell structures, which are widely developed in the Taili area of the west Liaoning Province in China. Statistical analysis of the SEC resulted in intervals of four types of competent layers, that is, Medium-scale Granitic coarse-to-pegmatitic Veins, Small-scale Augen Granite aplite Veins, Small-scale Granite aplite Veins, and Small-scale Augen Quartz–K-feldspar veins, with intervals of [3.50,  4.63], [2.64,  4.29], [2.70,  3.51], and [2.50,  3.36] respectively. The preferred intervals of VCM of the five types of pinch-and-swell structures, Small-scale Augen Granite aplite Veins + Fine-grained Biotite–Hornblende–plagioclase Gneiss, Medium-scale Granitic coarse-to-pegmatitic Veins + Fine-grained Biotite–Hornblende–plagioclase Gneiss, Small-scale Augen Granite aplite Veins + medium-to-fine-grained granitic gneiss, Medium-scale Granitic coarse-to-pegmatitic Veins + medium-to-fine-grained granitic gneiss, and Small-scale Augen Granite aplite Veins + fine-grained biotite–plagioclase gneiss, are [19.98,  62.51], [15.90,  61.17], [26.72,  93.27], [22.21,  107.26], and [76.33,  309.39] respectively. The similarities between these calculated SEC statistical preferred intervals and the physical experimental results verify the validity of the PSRG. The competent layers of the pinch-and-swell structures were presented in this study as power-law flow with SEC values that increased with the thickness of the layer. Grain-size plays an important role in the rheology of pinch-and-swell structures. The results offer a case for the application of PSRG and determine the key rock rheological parameters of North China Craton for future related studies.